The association between aspects of psychological resilience and subtypes of depression: implications for focussed clinical treatment models. (2nd July 2016) - Sharpley, Christopher F.; Bitsika, Vicki; Jesulola, Emmanuel; Fitzpatrick, Kerry; Agnew, Linda L.
Abstract: Objective: The aim of this study was to explore the association between Psychological Resilience (PR) and depression at global, dichotomous and subcomponent levels. Methods: A sample of 330 participants (117 males and 213 females) was randomly recruited from an electorate in Australia and completed the Zung Self-rating Depression Scale (SDS) and Connors-Davidson Resilience Scale (CDRISC). Results: PR was significantly and inversely associated with total SDS score at a global level. Only one of the three CDRISC factors was significantly associated with total SDS score and also with three of four SDS depression subtypes. Conclusions: Because of the different nature and treatment requirements for depression subtypes, PR may be applicable to a limited range of depressed patients, particularly those who do not exhibit Anhedonia.